Evaluating community-based research: Hearing the views of student research partners - Cullinane, Mark; O'Sullivan, Siobhán (International Journal for Students as Partners, 2020)
Despite the increasing popularity in the academy of collaborative approaches to research, evaluating the impacts of Students-as-Partners (SaP) initiatives has thus far received less systematic attention. This paper presents an evaluation of a participatory community-based research project where academics partnered with 15 mature students in a socio-economically disadvantaged estate in the south of Ireland to co-construct a household survey and conduct field research to gather the views of fellow residents on the regeneration of their area. The paper reports the findings of a subsequent qualitative, participatory evaluation of the student’s experience of this partnership with academics and its impacts. The findings illuminate some of the benefits and challenges of community-based staff-student research partnerships and points to the imperatives of aligning institutional, funder, and community participants’ capacities and objectives throughout the research cycle and the importance of evaluation to inform good practice in community-based research.